2011
DOI: 10.5047/eps.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar cycle variations on oxygen green line emission rate over Kiso, Japan

Abstract: A sixteen year long dataset of mesospheric OI 557.7 nm green line nightglow emission rate, measured over Kiso (35.79 • N, 137.63• E), Japan using ground-based photometers is spectrally investigated using the HilbertHuang Transform (HHT). The spectrograms reveal the presence of semi-annual, annual and quasi-biennial oscillations in consonance with the results obtained from wavelet analysis in an earlier study. In addition, due to the use of the HHT, we have been able to investigate the very low frequency sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
1
15
0
2
Order By: Relevance
“…Therefore, it cannot be expected that solar maximum/minimum ratios are independent of solar local time. This was confirmed by Das et al [], who found that the solar cycle impact on the green line emission rate is dependent on the local time, changing from 15% to 30% during the night and reaching its maximum at midnight.…”
Section: Solar Cycle Impactsupporting
confidence: 63%
See 1 more Smart Citation
“…Therefore, it cannot be expected that solar maximum/minimum ratios are independent of solar local time. This was confirmed by Das et al [], who found that the solar cycle impact on the green line emission rate is dependent on the local time, changing from 15% to 30% during the night and reaching its maximum at midnight.…”
Section: Solar Cycle Impactsupporting
confidence: 63%
“…These differences might also be related to the different local time sampling of the two instruments, because SCIAMACHY data covers a fixed local time only, whereas WINDII data covers all local solar times during the night. A local time dependence of the 11 year solar cycle in the green line radiance was indeed observed by the ground‐based measurements at Kiso (35.79°N, 137.63°E) [ Das et al , ] indicating around 40% solar maximum/minimum differences. The Buckland Park Field station (34.6°S, 138.6°E) observed the solar maximum/minimum differences of around 34 ± 14% [ Reid et al , ].…”
Section: Solar Cycle Impactmentioning
confidence: 68%
“…Rajesh et al [23], have reported the ionospheric plasma depletion phenomenon over Kavalur i.e., Indian low latitude station using the nighttime airglow intensity measurements at 557.7 nm. Effect of seasonal, solar cycle variation and determination of different range of periodicities from a few days to less than one solar cycle on nighttime airglow intensity of 557.7 nm over Kiso, was also described by Das et al [24,25]. But earlier workers have not attempted to such rare studies on long-term trend behavior on nighttime airglow emission intensity at 557.7 nm.…”
Section: Introductionmentioning
confidence: 85%
“…Thus, studies of long-term variation on mesospheric airglow specifically based on experimentally observed data and its possible causes are either rare or few [23][24][25]. Rajesh et al [23], have reported the ionospheric plasma depletion phenomenon over Kavalur i.e., Indian low latitude station using the nighttime airglow intensity measurements at 557.7 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is expected that airglow intensity would also change in response to solar variations. There have been quite a few studies on airglow intensity or airglow temperature variations caused by the 11-year solar cycles using airglow observations [Scheer et al, 2005;Azeem et al, 2007;Pertsev and Perminov, 2008;Beig et al, 2008;Das et al, 2011]; however, no definitive correlation has been established.…”
Section: Introductionmentioning
confidence: 99%